Effect of gas–liquid separation chamber and reflux hole on the self-priming performance of a self-priming pump - Yu-Liang Zhang; Hui-Fan Huang; Kai-Yuan Zhang; You-Qu Zheng (Scientific Reports)
Abstract To investigate the influence of changes in the geometric parameters of the gas–liquid separation chamber and reflux holes on the self-priming performance of the pump, this study innovatively establishes a recirculating pipeline system that includes a self-priming pump. This setup takes into account the impact during the speed increase phase. The, unsteady incompressible viscous flow for the complete self-priming process were performed using the volume of fluid (VOF) two-phase flow model and the Realizable k-ε turbulence model. The results indicate that the self-priming process can be divided into three stages: rapid suction stage, oscillatory gas discharge stage, and water intake and gas discharge stage. During the oscillatory gas discharge stage, the liquid involved in the gas-liquid mixture near the outer edge of the impeller is mainly supplied by the reflux hole. The water intake and gas discharge stage occupies the largest proportion of the entire self-priming process. The smallest volume gas-liquid separation chamber requires the least amount of gas to be discharged and has the lowest degree of internal gas dispersion, achieving self-priming first. Reflux hole with larger areas provide more liquid for the gas-liquid mixture, enhancing the efficiency of gas discharge during the early phase of the oscillatory gas discharge stage and the initial part of the water intake and gas discharge stage.